Dampak Lingkungan Kerja Sosial dan Insentif Pada Semangat Kerja Karyawan Industri Pariwisata - Nugroho, Muhammad Rizal; Senen, Syamsul Hadi; Tarmedi, Eded (Strategic : Jurnal Pendidikan Manajemen Bisnis, 2018)
The pupose of this paper is to find out influence social work environment and incentives against employee morale. The design of the research is a cross-sectional design. This research use descriptive and verificative approach with survey method. A total of 84 respondents were chosen as a simple random sampling. A survey questionnaire was used as research instrument to collect the data from respondents. Data analisys techniquesused in this research is multiple linier regression. The environmental impact of social work and incentives on employee morale tourism industry. The paper provides a basis to understand the issues of employ morale, incentivess and social work enviromental of tourism industrial. The difference of this study with previous research on objects that are used , the variable used , supporting the theory as well as the different references used by previous researchers